ROOTING PATTERN AND NITROGEN USE EFFICIENCY IN COTTON (GOSSYPIUM HIRSUTUM L.) UNDER MOISTURE STRESS CONDITIONS - Mahmood-ul-Hassan; M. Maqsood; S. A. Wajid; A.M. Ranjha (Journal of Animal and Plant Sciences, 2015)
Roots play an important role in exploring the plant’s ability to explore the available soil volume for water and nutrients. Among abiotic stresses, moisture stress is one of the most imperative factor that exerts substantial impact on root growth, nutrients use efficiency, and seed cotton yield. Field experiments were conducted during 2008-09, to elucidate the effect of moisture stress on rooting pattern, seed cotton yield, and nitrogen use efficiency (NUE) of different genotypes grown in alkaline calcareous soils. Three factors were: {three genotypesviz.V1 = NIAB-846, V2 = NIAB-824, and V3 = CIM-496); four moisture stresses(viz.I1 = local control-eight irrigations (all applied at 50% available soil moisture depletion level, ASMDL),I2 = moisture stress at inter-node elongation stage- in July up to 80% ASMDL, I3 = moisture stress at vegetative growth stage- in September up to 80% ASMDL,and I4 = moisture stress at inter-node elongation and at vegetative growth stage-in July and September up to 80% ASMDL)); and three nitrogen doses (viz. N1 = 50 kg ha-1, N2 = 100 kg ha-1, and N3 = 150 kg ha-1.)}arranged in Randomized Completed Block Design with split-split plot arrangements replicated thrice while keeping genotypes in main plots, moisture stresses in split plots, and nitrogen levels in split-split plots. Interaction treatments (I×N×V) significantly affected root:shoot ratio, seed cotton yield, and NUE. During 2008, highest root:shoot ratio (0.413) was recorded in NIAB-824 byI2×N1×V2 followed by 0.333 root:shoot ratio in NIAB-846 byI2×N1×V1treatment.During 2009, highest root:shoot ratio (0.412) was recorded in CIM-496 by I3×N1×V3treatment. Under higher N dose (150 kg N ha-1), root:shoot ratio didn’t vary significantly by different moisture stress treatments in all genotypes. Results showed that, highest seed cotton yield of 4871 and 4853 kg ha-1 was achieved in NIAB-846 and NIAB-824 by I3×N3×V2 and I1×N2 ×V2, respectively (during 2008);and 5709 and 5634 kg ha-1in NIAB-824 by treatments I3×N3×V2 and I1×N2×V2,(during 2009), respectively. During 2008, highest NUE of 105.09, 92.92, and 92.54 kg yield kg-1 N applied was obtained in I1×N1×V1, I1×N1×V2, I3×N1×V3, respectively. Similar trend was observed during 2009 with highest NUE in I1 and I3 treatments. Non-significant difference in highest NUE in no stress (control) and moisture stress at vegetative growth stage was observed. These results led towards the conclusion that N application @50 kg ha-1under moisture stress either in July or September causes higher root:shoot ratio in cotton genotypes and highest NUE in these genotypes can be achieved by imposing moisture stress at vegetative growth stage in September (by skipping one irrigation)coupled with 50 kg N ha-1.
Keywords: Moisture stress; Gossypium hirsutum L.; rooting pattern; nitrogen use efficiency